Antiretroviral Treatment Scale-Up and Tuberculosis Mortality in High TB/HIV Burden Countries: An Econometric Analysis. - Isabel Yan; Eran Bendavid; Eline L Korenromp (PLoS ONE, 2016)
Antiretroviral therapy (ART) reduces mortality in patients with active tuberculosis (TB), but the population-level relationship between ART coverage and TB mortality is untested. We estimated the reduction in population-level TB mortality that can be attributed to increasing ART coverage across 41 high HIV-TB burden countries.We compiled TB mortality trends between 1996 and 2011 from two sources: (1) national program-reported TB death notifications, adjusted for annual TB case detection rates, and (2) WHO TB mortality estimates. National coverage with ART, as proportion of HIV-infected people in need, was obtained from UNAIDS. We applied panel linear regressions controlling for HIV prevalence (5-year lagged), coverage of TB interventions (estimated by WHO and UNAIDS), gross domestic product per capita, health spending from domestic sources, urbanization, and country fixed effects.Models suggest that that increasing ART coverage was followed by reduced TB mortality, across multiple specifications. For death notifications at 2 to 5 years following a given ART scale-up, a 1% increase in ART coverage predicted 0.95% faster mortality rate decline (p = 0.002); resulting in 27% fewer TB deaths in 2011 alone than would have occurred without ART. Based on WHO death estimates, a 1% increase in ART predicted a 1.0% reduced TB death rate (p<0.001), and 31% fewer deaths in 2011. TB mortality was higher at higher HIV prevalence (p<0.001), but not related to coverage of isoniazid preventive therapy, cotrimoxazole preventive therapy, or other covariates.This econometric analysis supports a substantial impact of ART on population-level TB mortality realized already within the first decade of ART scale-up, that is apparent despite variable-quality mortality data.